How investor status affects judgments of management credibility: The role of company identification and locus of attribution - Peek, Erik; van Rinsum, Marcel; Stirnkorb, Sebastian (Contemporary Accounting Research, 2025)
Abstract This study investigates the joint effects of investor status and locus of attribution on investors' judgments of management credibility. We study these effects in the context of an adverse event disclosure. Building on social identity and ultimate attribution error theory, we predict and find that under external attribution, current investors perceive management as more credible than prospective investors do. In contrast, we predict and find that investor status does not affect perceived management credibility under internal attribution. We provide evidence supporting our theory that company identification explains these findings. In addition, we document that the differences in credibility are mainly driven by perceptions of management's trustworthiness, rather than competence. Moreover, our results indicate that these differences in credibility judgments affect earnings expectations, thus inducing disagreement among investors. Our findings have important practical implications, including that company identification can be an asset to companies and that communicating adverse events with an external attribution reduces perceived management credibility for prospective investors.